Issue Information. Issue 2 (5th February 2023) - Unknown
Abstract : Cover Illustration An Ad‐HSA/FA‐MβCD supramolecular complex significantly prolonged the blood retention of FA‐MβCD and improved its antitumor effect and safety after intravenous administration in tumor‐bearing nude mice xenografted with FR‐expressing cancer cells. Image: Kateryna Kon/Shutterstock.com. See article by Sakai et al., pp. 233–245 .